2020
DOI: 10.1021/acs.jpcc.0c09495
|View full text |Cite
|
Sign up to set email alerts
|

A Density Functional Theory Study on the Mechanism of Complete Ethanol Oxidation on Ir(100): Surface Diffusion-Controlled C–C Bond Cleavage

Abstract: Effective C−C bond cleavage is a critical concern in the applications of ethanol technologies. The lack of catalytic efficiency toward complete ethanol oxidation reaction (EOR) has hindered the development of direct ethanol fuel cells. Ir-based catalysts have recently shown promise in the complete EOR. However, its catalytic mechanism remains unclear, which impedes the development of better Ir-based catalysts. Herein, we report a comprehensive reaction network of complete ethanol decomposition on Ir(100) based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(82 citation statements)
references
References 73 publications
3
79
0
Order By: Relevance
“…A C–C bond cleavage in ethane decomposition without the presence of any other reactants can take place through one of the 10 elementary reactions summarized in Table S1. Among them, the C–C bond cleavages of CH 2 C, CHC, and CC species were studied on Ir(100) previously . In this work, we performed DFT calculations for the seven remaining reactions on Ir(100).…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…A C–C bond cleavage in ethane decomposition without the presence of any other reactants can take place through one of the 10 elementary reactions summarized in Table S1. Among them, the C–C bond cleavages of CH 2 C, CHC, and CC species were studied on Ir(100) previously . In this work, we performed DFT calculations for the seven remaining reactions on Ir(100).…”
Section: Computational Detailsmentioning
confidence: 99%
“…The bottom two layers were fixed in optimization calculations, and the bottom three layers were fixed in frequency calculations. The same model catalysts were used in our previous studies. , …”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iridium (Ir) has attracted much attention recently due to its important role in the surface-sensitive electrocatalytic reactions such as alcohol oxidation, ammonia oxidation, oxygen evolution reaction, and so forth. , Specifically, ethanol oxidation reaction (EOR), serving as the anodic half-reaction of direct ethanol fuel cells which could be a promising sustainable portable power source, needs to promote its efficiency. Also, it has been demonstrated to benefit the catalysis performance through the addition or decoration of the Ir metallic component. ,, In detail, it was found that Ir could display excellent ability in breaking the C–C bond , and the C–H bond of ethanol molecule to form the so-called C1 intermediates (CO ad and CH x species), which could follow the so-called C1 reaction pathway and eventually result in the considerable conversion of ethanol into CO 2 . ,, Along this line, some Ir-based or Ir-contained EOR catalysts were reported either in acidic or alkaline media, such as PtIr–SnO 2 , IrSn/SnO 2 , and IrPd/C . Note that the pristine Ir itself can hardly exhibit EOR catalytic activity, which could be due to the poisoning effect from the as-generated CO ad and/or CH x species on the Ir surface.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been demonstrated to benefit the catalysis performance through the addition or decoration of the Ir metallic component. 3,10,11 In detail, it was found that Ir could display excellent ability in breaking the C−C bond 3,12 and the C−H bond of ethanol molecule 13 to form the so-called C1 intermediates (CO ad and CH x species), which could follow the so-called C1 reaction pathway and eventually result in the considerable conversion of ethanol into CO 2 . 1,10,13 Along this line, some Ir-based or Ir-contained EOR catalysts were reported either in acidic or alkaline media, such as PtIr− SnO 2 , 3 IrSn/SnO 2 , 14 and IrPd/C.…”
Section: Introductionmentioning
confidence: 99%